2017
DOI: 10.1042/cs20171292
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in endothelin type B receptor contribute to microvascular dysfunction in women who have had preeclampsia

Abstract: Microvascular dysfunction originating during a preeclamptic pregnancy persists postpartum and likely contributes to increased CVD risk in these women. One putative mechanism contributing to this dysfunction is increased vasoconstrictor sensitivity to endothelin-1 (ET-1), mediated by alterations in ET-1 receptor type-B (ETBR). We evaluated ET-1 sensitivity, ETAR and ETBR contributions to ET-1-mediated constriction, and the mechanistic role of ETBR in endothelium-dependent dilation in vivo in the microvasculatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
4
24
0
Order By: Relevance
“…Recently, our laboratory examined vasoconstrictor responses to ET-1 in the cutaneous microvasculature of women who had preeclampsia. In agreement with the animal findings, we found that formerly preeclamptic women had an exaggerated vasoconstrictor response to ET-1, mediated by dysregulation of the ET B R (83). When compared with women who had a normal pregnancy, women with a history of preeclampsia had reduced ET B R-mediated dilation, and, in fact, ET B R signaling contributed to vasoconstriction, presumably through increased ET B R protein expression in the vascular smooth muscle (Fig.…”
Section: Endothelin-1 Signalingsupporting
confidence: 89%
“…Recently, our laboratory examined vasoconstrictor responses to ET-1 in the cutaneous microvasculature of women who had preeclampsia. In agreement with the animal findings, we found that formerly preeclamptic women had an exaggerated vasoconstrictor response to ET-1, mediated by dysregulation of the ET B R (83). When compared with women who had a normal pregnancy, women with a history of preeclampsia had reduced ET B R-mediated dilation, and, in fact, ET B R signaling contributed to vasoconstriction, presumably through increased ET B R protein expression in the vascular smooth muscle (Fig.…”
Section: Endothelin-1 Signalingsupporting
confidence: 89%
“…28 Although women with preeclampsia appear asymptomatic after delivering the placenta, an underlying dysfunction in the blood vessels remains. 30 Women with a history of preeclampsia had a MACE in the 10 years following the birth in an affected pregnancy of 18.2% compared with 1.7% of women without preeclampsia. 32 A recent meta-analysis comprising 22 studies and over six million women concluded that preeclampsia was associated with a fourfold increase in future incident heart failure and a twofold increased risk of MACE.…”
Section: Preeclampsiamentioning
confidence: 98%
“…29 One study on microvascular dysfunction found that ET-1-mediated vasoconstriction was increased in the microvasculature of women with a history of preeclampsia. 30 This may be attributed to the absence of ET-1 receptor type-Bmediated dilation, leading to an exaggerated vasoconstrictive response to ET-1. 30 Flow-mediated dilation is also abnormal with preeclampsia.…”
Section: Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic and uterine vasculature are refractory to vasoconstrictions during pregnancy. In contrast, enhanced contractile responses to vasoconstrictors is a characteristic feature of preeclampsia ( Naden & Rosenfeld 1981 , Magness & Rosenfeld 1986 , Benoit et al 2007 , Stanhewicz et al 2017 ). Elevated testosterone during pregnancy is shown to enhance contractile responses to many vasoconstrictors in endothelium-intact vessels, but in endothelium-denuded vessels, there is enhanced contractile response specific to angiotensin II in rat mesenteric ( Chinnathambi et al 2014 b ) and uterine arteries ( Chinnathambi et al 2014 a ).…”
Section: Testosterone-induced Mechanisms Of Vascular Dysfunction Durimentioning
confidence: 99%